Providing a Hybrid Methodology to Solve the Supplier Selection Problems: Application of MCDM Techniques - Agus Widodo; Pinar Aytekin; Shahryar Ghorbani; Media Rahmawati (International Journal of Supply Chain Management, 2020)
The emphasis of supply chain management (SCM) is majorly on the relationship between enterprise alliance and core enterprise. One of the main decision-making problems in SCM is choosing strategic partners, which also is the key to a prosperous SCM. In the present study, SCM is investigated using the analytical hierarchy process (AHP) simulation approach o examine the uncertainty involved in AHP and reduce its risk to some extent. Finally, this approach is employed to solve the problem of supplier selection in SCM.